Experimental and numerical analyses of leakage flux distribution in core-type voltage transformers - (:unkn) unknown (Electromagnetics Academy, 2015)
This study is based on leakage magnetic flux analysis of a core type transformer. The distributions that obtained experimentally were compared with two-dimensional FDM and FEM calculation results to verify. The experiment set includes a voltage transformer and measurement coils that are used to determine leakage flux distribution around of transformer iron leg. With the solution of the matrix created by measuring the induced voltage, polynomial mathematical equations were obtained. Then flux values have been calculated in accordance with the numerical methods. In order to compare the results, plotting of the flux distribution is the best solution. For this purpose, total flux lines was determined. In addition, the difference between the smallest and largest value of the vector potential is also determined. The voltage (potential difference) vector is calculated by dividing the difference to flux lines. In the last step, the equipotential points were determined by adding to the minimum potential value. This process was repeated for eight different heights in the legs and two-dimensional coordinates of the equipotential point was determined at each height. By combining the same valuable points, flux distribution was obtained graphically. Finally, fluxes have been drawn in line with the measurement and calculation results, and have been compared with each other. As a result, leakage flux distribution of voltage transformer is obtained and it is observed that FEM calculates closer values to the measurements. According to the study results, the using of the measurements from several points taken with magnetic field probes in FEM model, can provide sufficient accuracy solutions.